Asymmetric Tibial Component Improved the Coverage and Rotation of the Tibial Component in a Medial Pivot Total Knee Prosthesis - Minoda, Yukihide; Ikebuchi, Mitsuhiko; Mizokawa, Shigekazu; Ohta, Yoichi; Nakamura, Hiroaki (The Journal of Knee Surgery, 2018)
Malrotation of tibial components is one of the important causes of failure in total knee arthroplasty. The aim of this study is to determine the relationship between tibial rotational positioning and coverage of the tibial surface during the operation, using a symmetric and newly introduced asymmetric medial pivot tibial components. The coverage and overhang were compared between a symmetric component (Advance medial pivot) and a newly introduced asymmetric medial pivot tibial component (Evolution medial pivot) in 31 knees during the operation. When the tibial component was placed parallel to the anteroposterior (AP) axis, the uncovered width in the posteromedial part using a symmetric design was larger than that using an asymmetric design (p < 0.01). Overhang in the posterolateral part was observed in 42% for a symmetric design and 3% for an asymmetric design (p < 0.01). When the component was placed in malrotation (10 degrees internal to the AP axis), overhang in the posteromedial part was observed in 6% for a symmetric design and in 71% for an asymmetric design (p < 0.01). The tibial rotation parallel to the AP axis and maximizing coverage of the tibial surface conflict in a symmetric design, but are compatible in an asymmetric design. An asymmetric tibial component is expected to improve the coverage and the rotational positioning of medial pivot total knee prosthesis.
Keywords: medial pivot total knee prosthesis; asymmetric tibial component; tibial coverage; overhang